Growth, Photosynthesis, Solute Accumulation, and Ion Balance of Tomato Plant under Sodium‐ or Potassium‐Salt Stress and Alkali Stress. (1st March 2015) - Wang, Xiaoping; Geng, Shujuan; Ma, Yiqiao; Shi, Decheng; Yang, Chunwu; Wang, Huan
Abstract : In this study, tomato ( Lycopersicon esculentum Mill.) plant seedlings were subjected to Na‐ or K‐salt stress and Na‐ or K‐alkali stress. The growth, photosynthesis, and concentrations of solutes and inorganic ions in dry samples of stressed seedlings were measured to identify the physiological adaptive mechanisms by which tomato plants tolerate alkali stresses. The results showed that alkali stresses (Na‐ and K‐alkali stresses) significantly inhibited growth and photosynthesis, and the inhibitory effects of K‐salt stress on photosynthesis were greater for Na‐salt stress. The ions accumulation and balance were closely related to types of salts which were applied to. Under Na‐salt stress, Na +, K + and Cl − were the main osmolytes in both the roots and leaves, whereas K‐salt stress decreased the contribution of Na + and increased the contribution of K + . In the stems, the contribution of NO3 − increased under all stresses. Compared to salt stresses, the alkali stresses decreased the contribution of Cl − and increased the contribution of organic acids (OAs) in the stems and leaves. However, the roots revealed a different mechanism of ion accumulation and governing ionic balance. In addition to Na +, K + and OAs, the contributions of Ca 2+ and Mg 2+ should not be ignored. Although K and Na possess similar atomic characteristic, consisting with osmotic or high‐pH stress, they showed a distinct effect on plant photosynthesis and ion accumulation.